The Fabrication of GaN Nanostructures Using Cost-Effective Methods for Application in Water Splitting - Xin Xi; Lixia Zhao; Tuo Li; Xiaodong Li; Chao Yang (Crystals, 2023)
The adjustable bandgap, single crystal structure, and strong chemical inertness of GaN materials make them excellent candidates for water splitting applications. The fabrication of GaN nanostructures can enhance their water splitting performance by increasing their surface area, improving photon absorption, and accelerating photocatalytic reactions. Developing cost-effective methods to fabricate GaN nanostructures is crucial to promote the development of GaN-based materials in water splitting applications. In this review, we introduce the main cost-effective techniques for the fabrication of GaN nanostructures and highlight future development directions.